2014
DOI: 10.1063/1.4898372
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence spectroscopy of UV-MALDI matrices and implications of ionization mechanisms

Abstract: Matrix-assisted laser desorption ionization (MALDI) has been widely used in the mass analysis of biomolecules; however, there are a lot of debates about the ionization mechanisms. Previous studies have indicated that S1-S1 annihilation might be a key process in the generation of primary ions. This study investigates S1-S1 annihilation by examining the time-resolved fluorescence spectra of 12 matrices. No S1-S1 annihilation was observed in six of these matrices (3-hydroxy-picolinic acid, 6-aza-2-thiothymine, 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…However, they showed only a short, noisy part of the decay. As we reported even at low fluence high‐quality decay curves demonstrate both non‐exponentiality at short times, and a pronounced biexponential decay at times beyond the cutoff in Lin et al .,. We also found that the purity of commercial THAP dramatically affected the decay curves, as did the solvent used to prepare the samples.…”
Section: Pooling Rate Constantssupporting
confidence: 72%
See 2 more Smart Citations
“…However, they showed only a short, noisy part of the decay. As we reported even at low fluence high‐quality decay curves demonstrate both non‐exponentiality at short times, and a pronounced biexponential decay at times beyond the cutoff in Lin et al .,. We also found that the purity of commercial THAP dramatically affected the decay curves, as did the solvent used to prepare the samples.…”
Section: Pooling Rate Constantssupporting
confidence: 72%
“…Chen and Ni note that the Ni group has reported pooling rate constants in a different ratio than we proposed . Currently, one of us (R. K.) is conducting a new study of DHB isomers, including fluence dependence of emission yields and photodynamics.…”
Section: Pooling Rate Constantsmentioning
confidence: 75%
See 1 more Smart Citation
“…In this model, S 1 -S 1 annihilation is the first key step to ion generation. However, recent studies (59,60) have shown that numerous matrices do not undergo S 1 -S 1 annihilation. Another example is the contribution from preformed ions.…”
Section: Possible Contribution From Other Ionization Mechanismsmentioning
confidence: 98%
“…These and earlier values were used to argue that the CPCD cannot be correct because it is claimed to predict yields that are too high [4,[26][27][28]. Here, we use the newest data to revise the S n + S 1 pooling rate constants, and to test the revised model against the data for DHB and CHCA matrices.…”
mentioning
confidence: 99%